2015
DOI: 10.1021/acsami.5b04820
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-Mediated Interfacial Assembly of rGO-ZnO Nanostructures: A Bio-inspired Approach and Enhanced Photocatalytic Properties

Abstract: A bio-inspired approach for the fabrication of reduced graphene oxide (rGO) embedded ZnO nanostructure has been attempted to address issues pertaining to charge recombination and photocorrosion in ZnO for application as an effective photocatalyst. Herein we demonstrate the synthesis of rGO-ZnO nanostructures in a single step using polyamines, which simultaneously aid in the mineralization of ZnO nanostructures from zinc nitrate, reduction of graphene oxide (GO), and finally their assembly to form rGO-ZnO compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…When the thickness of the carbon shell is greater than 2 nm, the reaction rate is even slower than for pure TiO 2 . The catalytic efficiency of the photocatalysts was verified again for the photodegradation of other organic compounds of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 rhodamine B (RhB), 52 as TiO 2 @C with ~4 and ~8 nm carbon layers have the highest BET surface area, and therefore the largest capacity to adsorb reactants, but the lowest activity for photodegradation.…”
Section: Characterization Of Tio 2 @C Nanohybridsmentioning
confidence: 80%
See 3 more Smart Citations
“…When the thickness of the carbon shell is greater than 2 nm, the reaction rate is even slower than for pure TiO 2 . The catalytic efficiency of the photocatalysts was verified again for the photodegradation of other organic compounds of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 rhodamine B (RhB), 52 as TiO 2 @C with ~4 and ~8 nm carbon layers have the highest BET surface area, and therefore the largest capacity to adsorb reactants, but the lowest activity for photodegradation.…”
Section: Characterization Of Tio 2 @C Nanohybridsmentioning
confidence: 80%
“…It has been reported that 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 photogenerated holes can react with the surface oxygen atoms of an inorganic oxide photocatalyst, leading to an activity decrease. 52,56 At the oxide-carbon interface, interfacial C-O bonds can prevent the activation of the surface oxygen atoms by the holes, therefore leading to an improved photostability. 52,56 Accordingly, the good catalytic stability for the TiO 2 @C sample is likely to be attributed to the strong interfacial interaction between TiO 2 and C layer as implied in its Raman spectra (Figure 2-d).…”
Section: Photocatalytic Property Of Tio 2 @C Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The PL spectroscopy is usually used to investigate the seperation of the photo-induced electron-hole pairs in semiconductor photocatalysts [53,54]. Generally, the weaker is a PL spectra signal, the higher is separation efficiency of photo-induced electron-hole pairs.…”
Section: Pl Spectramentioning
confidence: 99%